Catalytic Oxidation of Methylene Blue by Attapulgite/TiO2 - Shang, Jianping; Jiang, Yu; Qin, Xiaoping; Zhao, Bin; Li, Xuefei (Frontiers in Environmental Science, 2021)
Methylene blue(MB) is a common pollutant in wastewater of printing and dyeing. At present, ozone oxidation is commonly used in the treatment of printing and dyeing wastewater. Ozone is oxidized by direct reaction and indirect reaction, However, the reaction rate is not high and it is impossible to completely mineralize organic matter. The experimental scheme is to impregnate the attapulgite(ATP) with a volume of tetrabutyl titanate-ethanol solution. The TiO2/attapulgite nanocomposite with high catalytic activity was prepared. The synthesized samples were subjected to characterized by X-Ray diffraction(XRD). The morphology and particle size of the particles were observed by scanning electron microscopy (SEM). The attapulgite modified by TiO2 was calcined at 300 °C for 2 h, and the degradation rate of 80 mg/L methylene blue was 99.8%. The experimental results show that the ozone, temperature and mass transfer factors are excluded, and the effects of temperature, MB concentration and pH on the degradation of methylene blue are investigated. The optimal reaction conditions are as follows: The ozone concentration is 0.067 g/min; the ozone flow rate is 0.15 NL/min; the stirrer rotation speed is 550 r/min; the catalyst is 0.1 g; the temperature is 50 °C; Based on the results, the reaction mechanism was derived and the kinetic study of the experiment was carried out.